العلاقات السعودية الماليزية المعاصرة: دراسة وثائقية تحليلية - شهري، خالد بن عبد الرحمن فايز (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The study of the relationship, at its various levels, between the Kingdom of Saudi Arabia and Malaysia is very important, due to their positions among the nations of the world economically, culturally and politically. The Kingdom of Saudi Arabia, for example, is an active key economic power in the world, given its membership in the G-20, coupled with it being a key place of the descent of Islamic revelations. Malaysia represents an evolving Islamic model and economic power in Southeast Asia. A study of this nature corrects the stereotypical image in the eyes of many that these relationships are confined to the Kingdom of Saudi Arabian tourists to Malaysia and the Malaysian pilgrims to the Kingdom of Saudi Arabia. This research has addressed the answer to the ultimate question:How have the Saudi-Malaysian relations evolved in the religious, political, economic and cultural fields?The researcher adopted the descriptive historical approach by relying on the documents obtained in both Saudi Arabia and Malaysia, as well as interviews conducted with some influential figures who have contributed immensely towards the betterment of these relationships.The study has concluded a number of findings and recommendations, including the Saudi-Malaysian relations are progressing steadily; the two countries should cooperate to facilitate ways to strengthen religious relations performance of Hajj and Umrah, and the training of judges and advocates, as well as the investment of political, economic and cultural opportunities to keep up with the development of human life in this era.